Long-term Hydrometeorological Time-series Analysis over the Central Highland of West Papua - Herho, Sandy H. S; Irawan, Dasapta E.; Kapid, Rubiyanto; Kaban, Siti N. (International Journal of Data Science, 2023)
This article presents an innovative data-driven approach for examining long-term temporal rainfall patterns in the central highlands of West Papua, Indonesia. We utilized wavelet transforms to identify signs of a negative temporal correlation between the El Niño-Southern Oscillation (ENSO) and the 12-month Standardized Precipitation Index (SPI-12). Based on this cause-and-eﬀect relationship, we employed dynamic causality modeling using the Nonlinear Autoregressive with Exogenous input (NARX) model to predict SPI-12. The Multivariate ENSO Index (MEI) was used as an attribute variable in this predictive framework. Consequently, this dynamic neural network model eﬀectively captured common patterns within the SPI-12 time series. The implications of this study are signiﬁcant for advancing data-driven precipitation models in regions characterized by intricate topography within the Indonesian Maritime Continent (IMC).